STUDY OF MICRONUCLI FREQUENCY IN DIFFERENT LEAD EXPOSED POPULATION - Ajanta Halder; Madhusnata De (The Malaysian Journal of Nursing (MJN), 2011)
Lead and lead compounds play a significant role in modern industry; a wide variety of population is at risk of occupational exposure and lead is suspected to be a human carcinogen. Chronic exposure to sub toxic levels of mutagenic metals is a cause of concern as such exposure has been seen to result in genetic modifications. Analysis of micronucleus (MN) in exfoliated buccal cells is a sensitive method for monitoring genetic damage in human population. In our study, we used four different occupational groups, Group l; Directly lead exposed garage workers (30 cases), Group 2; Directly exposed lead smelter factory workers (30 cases), Group 3; Indirectly lead exposed hospital staff (30 cases), Group 4;Control group (30 cases). We analysed MN frequencies in exfoliated buccal cells and compared the directly and indirectly exposed groups with control groups. The mean (±SD) MN(%) frequencies in exfoliated buccal cells from group 1 and 2 were 0.12±0.05 and 0.15±0.05 respectively and the mean (±SD) MN(%) frequencies in exfoliated buccal cells from group 3 and 4 were 0.06±0.04 and 0.05±0.04 respectively.